LITERATURE RECEPTION (A Conceptual Overview) - Ade Rahima (Jurnal Ilmiah Dikdaya, 2017)
The reception of literature has become an integral part of the purpose of the study of literature and literary reception are integrated into the definition of literature (literariness). Lately, various research literature incorporate literary reception in an effort to determine literariness. The literary output consists of text (for intra-textual relations system) in relation to extra-textual reality: with the norms of the literary, tradition and imagination. Reception theory is concerned reader responses that emerged after the reader interpret and judge a literary work. Literary reception arise due to stagnation intrinsic analysis for nearly half a century since the beginning of the 20th century. Literary reception can be done with concretization, distinguish between functions and functions realized. The first function is aimed to find the real author's intention. While the second function is the reader's reaction to literature. Two figures most instrumental in the development of the theory of literary reception is Robert Jauss and Wolfgang Iser. They show that the literary work can be studied empirically. Keywords : Literature, Reception